Medvedevittella nom. nov., a replacement for Gressittella Medvedev, 2009 (Coleoptera: Chrysomelidae) - Deng, Min; Xing, Jichun (Zootaxa, 2024)
The genus Gressittella belonging to the subfamily Eumolpinae Hope, 1840 (Coleoptera: Chrysomelidae), was established by Medvedev (2009), however, the name Gressittella Medvedev, 2009, is preoccupied by a leafhopper genus of the tribe Penthimiini (Hemiptera: Cicadellidae: Deltocephalinae) based on the type species Gressittella bella Evans, 1972. Thus, following article 60 of the International Code of Zoological Nomenclature (ICZN, 1999), Medvedevittella nom. nov., a new replacement name for the genus Gressittella Medvedev, 2009 (Coleoptera: Chrysomelidae) is proposed, and this results in four new combinations: Medvedevittella riedeli (Medvedev, 2009) comb. nov., Medvedevittella obscura (Medvedev, 2009) comb. nov., Medvedevittella laevis (Medvedev, 2009) comb. nov. and Medvedevittella foveipennis (Bryant, 1950) comb. nov., for the species currently included in this genus.